Risk Factors and Drug Therapy Monitoring in CKD Patients (Chronic Kidney Disease) - Patandung, Rosliana; Ishariyanto, Riski; Sune, Debi Mariska (Jurnal Impresi Indonesia, 2024)
Chronic Kidney Disease (CKD) is a global health problem that affects millions of people, characterized by a progressive decline in kidney function. This study aims to determine Drug Related Problems (DRPs) in the treatment management of CKD (Chronic Kidney Disease) patients. This study used the literature review method. The research results from the collected literature will be summarized and presented in the form of descriptive analysis. Researchers will conduct literature searches through online sites such as Google Scholar, PubMed, ResearchGate, Elsevier, and NCBI. The keywords used are “CKD risk factors” and “drug therapy for CKD patients”. The results of the search for relevant literature will be collected and selected according to the inclusion criteria. The research results from the collected literature will be presented in the form of a descriptive table. The table will include information such as author, year of publication, article title, and summary of the study results. The prevalence of drug-related problems (DRP) in CKD patients ranges from 12% to 87%. Commonly found problems include ineffective treatment, inappropriate drug selection, and drug dosing issues. Regular drug monitoring and dose adjustment are essential to reduce adverse drug reactions and improve patient outcomes. Effective drug therapy management and patient education are essential to improve the quality of care and life of CKD patients. In conclusion, this study emphasizes the importance of identifying and addressing drug-related problems (DRPs) to improve treatment effectiveness in CKD patients. Close drug monitoring and comprehensive patient education are key components in the optimal management of CKD.